2003
DOI: 10.1039/b211075j
|View full text |Cite
|
Sign up to set email alerts
|

Novel synthesis of highly active Pt/C cathode electrocatalyst for direct methanol fuel cell

Abstract: A 40 wt% Pt/C cathode electrocatalyst with controlled Pt particle size of ~2.9 nm showing better performance than commercial catalyst for direct methanol fuel cell was prepared by a polyol process with water but without using stabilizing agent.Pt-based electrocatalysts with high loading are usually employed in direct methanol fuel cells (DMFC) as cathode electrocatalysts for oxygen reduction reaction at relatively low temperature. Synthesis of highly dispersed supported platinum with uniform nanoparticle size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
109
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 243 publications
(114 citation statements)
references
References 16 publications
2
109
0
3
Order By: Relevance
“…Three-layer (substrate/diffusive/catalyst layer) gas diffusion electrodes were prepared according to literature [15][16][17]. The backing layers were loaded with 4 mg cm −2 of a mixture of carbon (Vulcan XC-72) and 10% PTFE.…”
Section: Catalyst and Electrode Preparationmentioning
confidence: 99%
“…Three-layer (substrate/diffusive/catalyst layer) gas diffusion electrodes were prepared according to literature [15][16][17]. The backing layers were loaded with 4 mg cm −2 of a mixture of carbon (Vulcan XC-72) and 10% PTFE.…”
Section: Catalyst and Electrode Preparationmentioning
confidence: 99%
“…Three-layer (substrate/diffusive/catalyst layer) gas diffusion electrodes were prepared according to literatures [15][16][17]. The backing layers were loaded with 4 mg cm −2 of a mixture of carbon (Vulcan XC-72) and 10% PTFE.…”
Section: Catalyst and Electrode Preparationmentioning
confidence: 99%
“…Although many studies in the literature can be found dealing with platinum deposited on carbon (among others), [24][25][26][27][28] fundamental research on the preparation of carbon-supported platinum catalysts is rather scarce. 5,[29][30][31][32][33][34][35] In our research on the application of platinum on CNF, we have compared the results obtained with an HDP method with those obtained with ion adsorption (IA), and we have investigated the extent of interaction between the dissolved metal precursor and the CNF support.…”
Section: Introductionmentioning
confidence: 99%